Periclimenes laevimanus sp. nov. from Vietnam, with a review of the Periclimenes granulimanus species group (Crustacea: Decapoda: Palaemonidae: Pontoniinae) - Ďuriš, Zdeněk (Zootaxa, 2010)
A new, hydroid-associated representative of the genus Periclimenes from Vietnam is described and illustrated. P. laevimanus sp. nov. is most similar to P. granulimanus Bruce, 1978, but differs from it by the more slender and smooth, not granulated, major second pereiopod and the non-dentate cutting edges of the minor second pereiopod. A new host is reported for P. granulimanus. Mouth parts are described and illustrated for P. brucei Ď uriš, 1990. This species is easily distinguished by its extremely elongate second pereiopods, with the carpus longer than the chela, and the walking legs lacking simple spines proximally from the distoventral series of paired spines. Periclimenes tonga Bruce, 1990 differs from other members of the species group by having only a single pair of dorsal telson spines. A key for the identification of species of the herein established P. granulimanus species group is provided. Types and/or museum specimens of some other Periclimenes species (P. hongkongensis Bruce, 1969, P. nomadophila Berggren, 1994, P. ruber Bruce, 1982, and P. toloensis Bruce, 1969) were examined to evaluate their relationship with the P. granulimanus species complex.